The right to mental health in armed conflict: A human rights framework for protection and compliance - Khaled Hassine (International Review of the Red Cross, 2026)
Abstract Mental health constitutes an integral and indivisible dimension of the right to the highest attainable standard of physical and mental health under international law. Yet, the specific obligations it generates for States in situations of armed conflict would benefit from a cross-sectoral discussion and engagement to enrich emerging understandings in both legal doctrine and institutional practice, with a view towards a comprehensive analytical framework. This article argues that the right to health framework, anchored in the International Covenant on Economic, Social and Cultural Rights and other core human rights treaties, provides a legally coherent and operationally applicable framework for the protection of mental health in armed conflict. It examines how the Availability, Accessibility, Acceptability and Quality framework, minimum core obligations, the requirement of non-retrogression and the duty to use maximum available resources operate in conditions of armed conflict. It also considers how to operationalize this framework, which recognizes affected persons as rights holders and engages legal responsibility of States as duty bearers as a condition for effective safeguarding of the right to mental health in armed conflict.